Preparation and study of CuBi2O4 thin films by RF magnetron sputtering. (October 2020) - Duployer, Benjamin; Tenailleau, Christophe; Thimont, Yohann; Lenormand, Pascal; Barnabé, Antoine; Presmanes, Lionel
Graphical abstract: Highlights: Preparation of the first RF-sputtered thin films of CuBi2 O4 . Pure crystalline CuBi2 O4 thin films was characterized by XRD and Raman spectroscopy. Optical measurements on CuBi2 O4 thin films prepared by PVD show a band gap of 1.5 eV. Abstract: Copper bismuth oxide (CuBi2 O4 or Bi2 CuO4 ) thin films have been elaborated for the first time by radio-frequency magnetron sputtering using a homemade CuBi2 O4 ceramic target. X-ray diffraction characterizations revealed an amourphous phase for as-deposited films. After air annealing at 450 °C for 12 h, a pure polycristalline CuBi2 O4 phase can been obtained. Raman spectroscopy confirmed the film phase purity. The influence of the thickness on the structural properties of the films has been studied and we observed that all films treated above 450 °C are crystallized. The thinner films show preferred orientation while there are less crystal defects for the thickest films (∼700 nm). Atomic force microscopy shows a homogeneous polycristalline microstructure at the surface of the film. Optical measurements performed by UV–vis-IR spectrophotometry indicate that these films have one of their optical band gaps in the visible region (Eg ∼1.5 eV) which makes them suitable as thin films solar absorption materials.